Bohemia, Literatura e Historia - Álvarez Sánchez, Jaime (Cuadernos de Historia Contemporánea, 2003)
This article intends to analize the literally origins of bohemian movement in France, its influences in Spanish context and the different ways of being part of the movement since it appeared, paying attention to its main features.